Programa educativo "icce" basado en la teoría sociocultural de vygotsky y las relaciones interpersonales de los estudiantes del quinto grado de primaria de la i.e. "simón bolívar" otuzco - la libertad 2012 - Rosas Quispe, Reynaldo (2016)
This research aims to demonstrate that the application of a system based on Vygotsky sociocultural theory program significantly improves interpersonal relationships of students in the 5th grade of Primary Education of Children of School Simon Bolivar City Otuzco. It worked only with one group: experimental (30 students). Using a quasi- experimental design contrasting control group pre and post measurement and; as pre - test and post - test to measure the level of interpersonal relationships: always, sometimes and never, a test of interpersonal relationships with 50 statements was used. In the experimental group based on Vygotsky sociocultural theory for 12 learning sessions, creating a climate of interpersonal relationships such program was implemented: integration, communication, cooperation and empathy; allowing students to actively participate in their learning and change their negative school behavior. The results show that the implementation of the education program based on Vygotsky sociocultural theory significantly improves interpersonal relationships of students in Elementary Education Minor